TLR9 independent interferon α production by neutrophils on NETosis in response to circulating chromatin, a key lupus autoantigen. Issue 12 (7th September 2013) - Lindau, Dennis; Mussard, Julie; Rabsteyn, Armin; Ribon, Matthieu; Kötter, Ina; Igney, Annette; J Adema, Gosse; Boissier, Marie-Christophe; Rammensee, Hans-Georg; Decker, Patrice
Abstract : Objectives: Interferon (IFN) α is a key immunoregulatory cytokine secreted by activated plasmacytoid dendritic cells (PDC) that constitute less than 1% of leucocytes. IFNα plays an important role in the pathogenesis of systemic lupus erythematosus (SLE). Nevertheless, the natural IFNα inducers in SLE as well as the different IFNα secreting cell types are only partially characterised. Methods: Chromatin was purified from calf thymus. Human peripheral blood mononuclear cells (PBMC), neutrophils and mouse bone marrow neutrophils were purified and cultured with different stimuli. IFNα production was estimated by flow cytometry, ELISA and a bioassay, and gene expression by quantitative real time PCR. Neutrophil activation and NETosis were analysed by flow cytometry, ELISA and confocal microscopy. Results: Neutrophils produced a bioactive IFNα on stimulation with purified chromatin. IFNα secretion was observed with steady state neutrophils purified from 56 independent healthy individuals and autoimmune patients in response to free chromatin and not chromatin containing immune complexes. Chromatin induced IFNα secretion occurred independently of Toll-like receptor 9 (TLR9). Neutrophil priming by granulocyte-colony stimulating factor, granulocyte macrophage-colony stimulating factor or IFNα was not necessary but PBMC sustained IFNα secretion by neutrophils. PDC were 27 times more efficient than neutrophils but blood neutrophils were 100 times more frequent than PDC. Finally, neutrophil activation by chromatin was associated with NETosis and DNA sensor upregulation. Conclusions: Neutrophils have the capability of producing IFNα on selective triggering, and we identified a natural lupus stimulus involved, unveiling a new mechanism involved in SLE. Neutrophils represent another important source of IFNα and important targets for future therapies aimed at influencing IFNα levels.